A 2-DOF nano-positioning scanner with novel compound decoupling-guiding mechanism. (January 2021) - Wang, Fujun; Zhao, Xiaolu; Huo, Zhichen; Shi, Beichao; Liang, Cunman; Tian, Yanling; Zhang, Dawei
Highlights: A 2-DOF compliant nano-positioning scanner featured with the novel compound decoupling-guiding mechanism is proposed. The chain-based compliance matrix method is adopted for analytical modeling. The proposed scanner shows a good input and output decoupling capacity, and the cross-axis coupling ratio is lower than 0.6%. Abstract: This paper presents the design and characteristic analysis of a novel two-degree-of-freedom (2-DOF) compliant nano-positioning scanner with novel compound decoupling-guiding mechanism. The mechanism features with the combination of separated prismatic joint and parallelogram, through which the parasitic displacement of scanner can be reduced and the motion guiding is obtained. Furthermore, the dynamic performance can be effectively improved. An amplifier and symmetrical configuration are adopted for decoupled motion with large stroke. An analytical model based on the modified matrix method is established to describe the static and dynamic characteristics, and the performance of the nano-positioning scanner is further analyzed by finite element method. A prototype of the scanner has been fabricated, and the experimental test is carried out. A PID controller is adopted to improve the linearity of motion. The results illustrate that the proposed scanner has a working range of 40.2×42.9 µm 2 with a small cross-axis coupling ratio below 0.6% and a positioning resolution of 10 nm.